DILEMA DUNIA PENDIDIKAN NASIONAL - Zulfakar, Zulfakar (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2019)
The changes that have occurred have shifted the order of life and the views of the people. Materialism, capitalism, efficiency, and effectiveness, have become the purpose and spirit of life. Shifting people’s views, has also changed the view of success and quality of education, where education is measured by success in the absorption of graduates in the world of work, therefore, education is analyzed from the characteristics of investment. Shifting the meaning and responsibility of education, encouraging the world of education to reform with alternatives: building renewal of reasoning of its citizens, towards independence and maturity, education is carried out comprehensively and collaboratively, with all parties in partnership, and build a vision of education comprehensively and simultaneously, with all parties. Keywords: Dilemma, World of National Education